FROM PEER CULTURE TO PERFORMANCE: EXPLORING HOW SUPPORTIVE VS. PRESSURING PEER NORMS INFLUENCE STUDY HABITS AND ACADEMIC ACHIEVEMENT AMONG UNIVERSITY STUDENTS. (Contemporary Journal of Social Science Review, 2025)
Peer culture constitutes a significant and proximal influence within higher education, shaping daily study decisions and ultimately affecting academic performance. In Pakistan's rapidly growing university sector, where formal support systems are inconsistently implemented, understanding how peer norms influence behavior is both urgent and actionable. This study quantitatively examines the relationships among supportive and pressuring peer cultures, students' study habits, and academic achievement, and identifies potential avenues for enhancement. The research utilized cross-sectional survey methodology targeting enrolled university students at the University of Sargodha. A stratified random sampling method was employed, followed by simple random selection within each stratum, resulting in a sample size of 200 participants. Data collection was conducted using a structured questionnaire incorporating 5-point Likert scales to assess the dimensions of supportive and pressuring peer culture, study habits, and academic achievement. The internal consistency of the questionnaire was evaluated using Cronbach's alpha, and the data were scrutinized for quality assurance. Data analysis was performed using descriptive statistics, Pearson correlation coefficients, hierarchical multiple regression analysis, and mediation testing via bootstrapped confidence intervals. Results indicate large, positive associations between study habits and achievement (r = .658, p < .001) and between peer culture and study habits (r = .606, p < .001), and a moderate correlation between peer culture and achievement (r = .499, p < .001). Study habits alone account for 43.3% of the variance in achievement (R² = .433); adding a supportive peer culture increases the explained variance to 50.9% (ΔR² = .076, p < .001), with negligible multicollinearity. The findings suggest two main practical strategies for universities: institutionalizing supportive peer norms, such as near-peer mentoring and structured study groups, and integrating study skills training into first-year curricula. Addressing both the social environment and the daily behaviors that facilitate learning provides a pathway to achieving measurable improvements in academic performance within Pakistan’s higher education institutions.